Types et trajectoires d’insertion socioprofessionnelle de jeunes diplômés: Caractéristiques et profil sociodémographique - Fournier, Genevieve; Pelletier, Rene; Beaucher, Chantale (Canadian Journal of Higher Education, 2002)
This article discusses the results of a study conducted toward young graduates from professional high school, technical college and university during the first three years of their socio-professional integration process. The purpose is to understand different events, personal and professional, that are significant when young graduates enter to the work market. Moreover, their professional situation three years after graduation is discussed. More closely, we present four types and eleven paths of socio- professional integration, identified from interviews carried out three years after graduation. By means of these interviews, we propose an analysis of the results according to the gender and level of education of the subjects. Finally, a discussion about the insidious form of professional instability for a growing proportion of graduates, as well as a reflection about the different groups that are more vulnerable to it, is presented.